1997
DOI: 10.1111/j.1151-2916.1997.tb03156.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Mullite from Filled Siloxanes

Abstract: Monolithic mullite with low sintering shrinkage was synthesized from polymer/filler blends-that is, siloxane/ alumina (siloxane/Al 2 O 3 ) (and siloxane/aluminum (siloxane/Al)) mixtures. The synthesis was based on a reactionbonding process of amorphous silica, which formed when the siloxane was oxidized, with Al 2 O 3 (or oxidized aluminum filler) at temperatures >1250°C. Thermodynamic calculations were used to calculate the phase composition at equilibrium. Thermoanalytical, infrared-spectroscopic, and micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 19 publications
4
42
0
3
Order By: Relevance
“…In this case, the fillers simply partially reduce the total shrinkage in the component, by diluting the transforming mass [6]. Oxide powders have rarely been added as fillers to produce all-oxide ceramics [7][8][9], probably due to the fact that typically preceramic polymers are processed in inert atmosphere in order to retain the C atoms which play a key role in the development of the unique microstructure and properties of PDCs [10]. However, some www.elsevier.com/locate/ceramint papers have very recently highlighted the potentialities of using such oxide fillers in combination with polymethylsiloxanes.…”
Section: Introductionmentioning
confidence: 98%
“…In this case, the fillers simply partially reduce the total shrinkage in the component, by diluting the transforming mass [6]. Oxide powders have rarely been added as fillers to produce all-oxide ceramics [7][8][9], probably due to the fact that typically preceramic polymers are processed in inert atmosphere in order to retain the C atoms which play a key role in the development of the unique microstructure and properties of PDCs [10]. However, some www.elsevier.com/locate/ceramint papers have very recently highlighted the potentialities of using such oxide fillers in combination with polymethylsiloxanes.…”
Section: Introductionmentioning
confidence: 98%
“…In the case of Al 2 O 3 reinforced samples, the formation of a mullite phase is common in this kind of materials and was also corroborated through infrared spectroscopy [12,20,21]. The formation of mullite inhibits the devitrification of the amorphous matrix [20] and gives as a result a decrease of the pure silica phase available to react with the free carbon phase in the carbothermal reduction.…”
Section: Discussionmentioning
confidence: 56%
“…2b), but the absence of the aluminum carbide-derived bands indicates that there are no reaction between the Al and C atoms, as occurs at low sintering temperatures when using aluminum as a filler and conventional ceramic route [7]. However, the presence of a sharp peak at 1160 cm À 1 in the spectra on the Al 2 O 3 reinforced samples is interpreted as a sign of formation of a mullite phase, as several authors reported [12,20,21]. Raman spectra of all the obtained nanocomposites show the typical bands of carbon-containing materials, the D and G bands in the first order spectra, and the non resolved resonance modes of the second order spectra, characteristics of highly disordered structures (Fig.…”
Section: Structural Characterizationmentioning
confidence: 80%
“…• C to facilitate mullite formation [106,107]. Kim et al adapted this approach to prepare partially interconnected open-cell microcellular mullite ceramics with cell densities greater than 10 9 cells cm −3 and cell size smaller than 20 µm from an Al 2 O 3 -filled polysiloxane [108].…”
Section: Reaction Technique For Matrixmentioning
confidence: 99%